Manajemen Strategis Lembaga Pendidikan Islam dalam Menghadapi Tantangan Global - Zakiah, Nurfitriani fitrotu; Prabaningtyas, Vina (Addabani: Interdisciplinary Journal of Islamic Education, 2023)
Globalization as a gate opens boundaries that allow the world to transact values, culture, knowledge, economy, and others. Globalization creates a world without barriers so that it has positive and negative impacts, including for Islamic educational institutions. Globalization provides openness for the wide spread of knowledge but also opens global currents that allow students to be affected by bad behavior such as juvenile delinquency. Globalization brings technological developments that can help improve the quality of education but can also be a threat if educational institutions are unable to develop the required skills. Therefore, Islamic educational institutions must use strategic management to face global challenges. The aim of this research is to reveal strategic management that can be applied in Islamic educational institutions in facing the era of globalization. The type of research used is a qualitative research method with a literature study research model. The results of this study found that the strategic management of Islamic educational institutions that can be carried out to face global challenges is to create technology-based educational institutions and strengthen character education.